A randomized, double‐blind, placebo‐ and positive‐controlled crossover study of the effects of durlobactam on cardiac repolarization in healthy subjects - O’Donnell, John (Clin Transl Sci, 2021)
Durlobactam (formerly ETX2514) is a diazabicyclooctane β‐lactamase inhibitor that inhibits class A, C, and D β‐lactamases. Sulbactam combined with durlobactam has in vitro and in vivo activity against Acinetobacter baumannii including carbapenem‐ and colistin‐resistant isolates and is being developed for treating serious infections due to A. baumannii. The effect of a single supratherapeutic dose of durlobactam on the heart rate corrected QT interval (QTc) was evaluated in healthy subjects in a placebo‐ and active‐controlled, single‐infusion, three‐way crossover study. Subjects were randomized to 1 of 6 sequences that included a single 3‐h i.v. infusion of durlobactam 4 g (supratherapeutic dose), a single 3‐h i.v. infusion of placebo, and a single 3‐h i.v. infusion of placebo plus a single oral dose of moxifloxacin 400 mg given open‐label at the end of the i.v. infusion. In each treatment period, Holter electrocardiogram (ECG) measurements were obtained from predose through 24 h post‐start of infusion. For the primary ECG end point, placebo‐corrected change‐from‐baseline corrected QT Fridericia’s formula (ΔΔQTcF), no significant change was observed with durlobactam. A concentration‐QT analysis demonstrated no significant effect of durlobactam on ECG parameters, including QT interval prolongation. Thus, durlobactam has a low risk for prolonging the QT interval and is unlikely to produce any proarrhythmic effects.